Baseline Body Composition and Physical Activity Level Recommended for Optimal Bone Mineral Density in Young Women - Sangun Lee; Chikako Fujita; Atsuko Satoh (Mary Ann Liebert, 2022)
Aim: This study examined the influence of body composition and physical activity level (PAL) on bone mineral density (BMD) to determine the baseline values necessary for maintaining healthy trabecular bone and improving bone health in young women. Materials and Methods: The subjects, consisting of healthy young women, were assigned to either a BMD-low (BMD-L) or BMD-high (BMD-H) group using the osteosonic index. PAL was measured for 1 week and rated on a scale from PAL-1 to 8 according to intensity levels (metabolic equivalents [METs]). The Wilcoxon rank-sum test was performed for intergroup comparisons. Results: The BMD-H group had significantly higher fat-free muscle mass, skeletal muscle index, and basic metabolic rate than the BMD-L group (p?<?0.001, each). Regarding the timing of physical activity in daily life according to intensity, PAL-6 (p?<?0.01), PAL-7 (p?<?0.001), and PAL-8 (p?<?0.01) for the BMD-H group were significantly longer than those for the BMD-L group. Discussion and Conclusion: For young women in their early 20s, BMD may be associated with baseline physical fitness and strength, as determined by body composition, but it is not influenced by the duration of physical activity. A PAL ?6.0 METs may improve or maintain the effect on BMD.